Myocardial oxygen consumption in aortic valve disease with and without left ventricular dysfunction. Issue 2 (February 1992) - Schwitter, J; Eberli, F R; Ritter, M; Turina, M; Krayenbuehl, H P
Abstract : OBJECTIVE–To assess whether and to what extent myocardial oxygen consumption is modified by hypertrophy and alterations in contractility in patients with aortic valve disease and to evaluate the influence of regression of left ventricular hypertrophy and improvement of contractility on myocardial oxygen consumption after successful aortic valve replacement. DESIGN–A cohort analytical study to investigate the influence of the "explanatory" variables of myocardial oxygen consumption by multiple regression analysis. A comparison of myocardial oxygen consumption in preoperative patients with that after operation in a group with comparable severity of aortic valve disease before operation (analysis of covariance). PATIENTS–In six controls and in 43 patients with aortic valve disease and normal coronary arteries standard haemodynamic variables were measured, left ventricular biplane cineangiography performed, and coronary sinus blood flow measured by thermodilution. The patients were divided into three groups: 19 preoperative patients with normal ejection fraction (greater than or equal to 57%) (group 1); nine preoperative patients with reduced ejection fraction (less than 57%) (group 2); 16 postoperative patients (one with preoperative and postoperative measurements (group 3). Postoperative evaluation was performed 12-51 months after surgery. MAIN OUTCOME MEASUREMENTS–Myocardial oxygen consumption/100 g left ventricular muscle mass and its suspected "explanatory" variables–that is, peak systolic left ventricular circumferential wall stress, heart rate, contractility (assessed by left ventricular ejection fraction), and left ventricular muscle mass index. RESULTS–Multiple regression analysis showed that the product of peak systolic stress and heart rate (p less than 0.0001) and ejection fraction (p less than 0.03) were positively correlated with myocardial oxygen consumption/100 g and that left ventricular muscle mass index (p less than 0.002) was negatively correlated with myocardial oxygen consumption/100 g (r = 0.72; n = 50 measurements). Myocardial oxygen consumption per 100 g at a given stress-rate product was higher in the controls than in group 1 (hypertrophied ventricles with normal ejection fraction) and was also higher in group 1 than in group 2 (hypertrophied ventricles with reduced ejection fraction). In a subgroup of the postoperative patients with complete regression of hypertrophy and normalisation of contractility, myocardial oxygen consumption per 100 g at a given stress-rate product was indistinguishable from that in controls. CONCLUSIONS–When the actual stress-rate product was used as an index of overall left ventricular performance the results suggested that mechanical efficiency was increased in hypertrophied ventricles especially when contractility was decreased. These changes in mechanical efficiency seemed to be reversible during the postoperative course when muscle mass and contractility returned to normal.